Probability, statistics, and reliability for engineers and scientists - Ayyub, Bilal M. (CRC Press, 2011)
IntroductionIntroduction Knowledge, Information, and Opinions Ignorance and Uncertainty Aleatory and Epistemic Uncertainties in System Abstraction Characterizing and Modeling Uncertainty Simulation for Uncertainty Analysis and Propagation Simulation Projects Data Description and TreatmentIntroduction Classification of Data Graphical Description of Data Histograms and Frequency Diagrams Descriptive Measures Applications Analysis of Simulated Data Simulation Projects Fundamentals of ProbabilityIntroduction Sets, Sample Spaces, and EventsMathematics of Probability Random Variables and Their Proba.
Keywords: Engineering mathematics.; Reliability (Engineering); elektronické knihy; electronic books